Learn From Home dalam Mengembangkan Keterampilan Dasar Mengajar Mahasiswa Calon Guru Biologi di Tengah Pandemi Covid-19 - Dwi Ratnasari (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2021)
The Covid-19 pandemic occurred several country, especially in Indonesia, it this had an impact on various fields. One of the areas affected in education, the face-to-face learning process must shift to distance learning using various digital means, so that learning continues to be carried out well. This study aims to analyze the learn from home (LFH) strategy during the Covid-19 pandemic in developing student teaching skills. The method used in this research is descriptive method, using instruments for assessing basic teaching skills. The sample used  Biology Education students, FKIP Untirta who took teaching competency development courses. The results of this study showed  the basic teaching skills of students when they learned from home in the Covid-19 pandemic were good (76.94). Students felt that LFH provided effectiveness and efficiency in developing basic teaching skills.